Analysis of the financing accounting system at pt. People's Bank of Indonesia (Persero) Tbk. Mardinata Manado sub-branch office - Julieta Monica Latumena (Journal on Economics, Management and Business Technology, 2023)
This study aims to analyze the effectiveness and suitability of the working capital credit financing accounting system at PT. Bank Rakyat Indonesia (Persero) Tbk, Martadinata Sub-Branch Office and find out whether PT. Bank Rakyat Indonesia (Persero) Tbk, Martadinata Sub-Branch Office has been carried out in accordance with the inclusion of banking financing accounting standards and procedures for providing applicable financing. This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk, Martadinata Manado Sub-Branch Office. The initial step taken by the author is field research in the form of a t-shirt study by visiting the research object, namely PT. Bank Rakyat Indonesia (Persero) Tbk, Martadinata Manado Sub-Branch Office. Next, the author collects data that will be used in research, namely in the form of primary data obtained by the author from the results of interviews with staff and employees of PT. Bank Rakyat Indonesia (Persero) Tbk, Martadinata Sub-Branch Office and secondary data obtained by the author through books, written reports obtained from companies such as company organizational structure, brief history of the company, and list of credit financing collectibility in 2014 and early 2015 and other literature in accordance with the purpose of writing. From this secondary data, the authors obtain theories that will be analyzed and evaluated with primary data, so that the authors can provide conclusions and suggestions. The data analysis technique used by the author is descriptive method. The findings from this analytical study, it can be concluded that PT. Bank Rakyat Indonesia (Persero).